Temperature and Substrate Requirement for Germination of Dicoccum Wheat - D.S. UPPAR; M.B. KURDIKERI; M.B. CHETTI; R.R. HANCHINAL; A.S. NALINI; S.D. SHASHIDHARA (Seed Research, 2026)
A laboratory study on germination of dicoccum wheat (cv. DDK-1009) indicated that the temperature of 20° C is better for the germination per cent and seedling length in husked seeds as compared to the dehusked seeds. Among the substrates, these parameters were more in between paper. Among the interaction effect the combination of temperature at 20°C with between paper recorded maximum values for germination parameters for both husked and dehusked seeds. However, the husked seeds recorded higher values for germination.